2021
DOI: 10.14704/nq.2021.19.8.nq21121
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Muscle Thickness and Echogenicity in the Diagnosis of Diabetic Peripheral Neuropathy

Abstract: Objectives: This study aims to find the thickness of muscles of lower limbs in patients with diabetic peripheral neuropathy (DPN) along with echogenicity and applying these two findings in the diagnosis of the disease. Methods: This is a case-control study conducted in the clinical neurophysiology unit in Merjan medical city. It includes 73 patients diagnosed to have DPN based on characteristic history and physical examination and documented by nerve conduction study. These patients are matched to 73 control t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…As mentioned by Resmini (2019) if the teacher wants to discuss a topic with the students, they can use first language in order to help the students struggle with English. In contrast to what has mentioned above, Kadhim et al, (2022) argued that the use of the first language in foreign language learning is currently considered taboo, because many educational institutions are trying to prohibit the use of the first language in foreign language classes. The use of L1 in ELL have many benefits, for example: reducing barriers to learning and increasing self-confidence in the learning process is one of the benefits of using L1, so that students can understand the target language being taught (Liando & Tatipang, 2022).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…As mentioned by Resmini (2019) if the teacher wants to discuss a topic with the students, they can use first language in order to help the students struggle with English. In contrast to what has mentioned above, Kadhim et al, (2022) argued that the use of the first language in foreign language learning is currently considered taboo, because many educational institutions are trying to prohibit the use of the first language in foreign language classes. The use of L1 in ELL have many benefits, for example: reducing barriers to learning and increasing self-confidence in the learning process is one of the benefits of using L1, so that students can understand the target language being taught (Liando & Tatipang, 2022).…”
Section: Introductionmentioning
confidence: 79%
“…As Kadhim et al, (2022) claimed that the mother tongue has a significant role in improving the students' English ability. In addition, the mother tongue provides a good role to clarify instruction, pronunciation and express their frustration or difficulties (Khasawneh, 2021).…”
Section: The Use Of First Language During English Lessonmentioning
confidence: 99%
“…A survey on the previous work carried out to find the best tool that has been used for the diagnosis of DPN and investigates the new techniques that can be combined on an integration system for the precise diagnosis system: Zahid et al in 2021 [11] showed that the muscle ultrasound as a valuable and complementary tool for the diagnosis of DPN, where the thickness and the echogenicity of lower limbs muscle ultrasound in patients with DPN and casecontrol study had been conducted alongside the NCS, physical examination and history characteristic of those groups. The outcome result was a statistically significant increase in the echogenicity and decrease in muscle thickness of tested patients compared with control group.…”
Section: Introductionmentioning
confidence: 99%